Contrasting Histopathology and Crystal Deposits in Kidneys of Idiopathic Stone Formers Who Produce Hydroxy Apatite, Brushite, or Calcium Oxalate Stones. Issue 4 (30th January 2014) - Evan, Andrew P.; Lingeman, James E.; Worcester, Elaine M.; Sommer, Andre J.; Phillips, Carrie L.; Williams, James C.; Coe, Fredric L.
ABSTRACT Our previous work has shown that stone formers who form calcium phosphate (CaP) stones that contain any brushite (BRSF) have a distinctive renal histopathology and surgical anatomy when compared with idiopathic calcium oxalate stone formers (ICSF). Here we report on another group of idiopathic CaP stone formers, those forming stone containing primarily hydroxyapatite, in order to clarify in what ways their pathology differs from BRSF and ICSF. Eleven hydroxyapatite stone formers (HASF) (2 males, 9 females) were studied using intra‐operative digital photography and biopsy of papillary and cortical regions to measure tissue changes associated with stone formation. Our main finding is that HASF and BRSF differ significantly from each other and that both differ greatly from ICSF. Both BRSF and ICSF patients have significant levels of Randall's plaque compared with HASF. Intra‐tubular deposit number is greater in HASF than BRSF and nonexistent in ICSF while deposit size is smaller in HASF than BRSF. Cortical pathology is distinctly greater in BRSF than HASF. Four attached stones were observed in HASF, three in 25 BRSF and 5–10 per ICSF patient. HASF and BRSF differ clinically in that both have higher average urine pH, supersaturation of CaP, and calcium excretion than ICSF. Our work suggests that HASF and BRSF are two distinct and separate diseases and both differ greatly from ICSF. Anat Rec, 297:731–748, 2014. © 2014 Wiley Periodicals, Inc.